Closed form solution for scheduling arbitrarily divisible load model in data grid applications: multiple sources - Abdullah, Monir; Othman, Mohamed; Ibrahim, Hamidah; K. Subramaniam, Shamala (Science Publications, 2009)
Scheduling an application in data grid was significantly complex and very challenging because of its heterogeneous in nature of the grid system. When the Divisible Load Theory (DLT) model had emerged as a powerful model for modeling data-intensive grid problem, Task Data Present(TDP) model was proposed based on it. This study presented a new Adaptive TDP (ATDP) for scheduling the intensive grid applications. New closed form solution for obtaining the load allocation was derived while computation speeds and communication links are heterogeneous. Experimental results showed that the proposed model can balance the load efficiently.